Hyaluronic acid/serotonin-decorated cerium dioxide nanomedicine for targeted treatment of ulcerative colitis. (9th December 2022) - Gao, Yanyao; Zou, Jing; Chen, Bo; Cao, Yuhao; Hu, Datao; Zhang, Yuchen; Zhao, Xinxin; Wen, Jinpeng; Liu, Kailai; Wang, Ke
Abstract : Mechanism of action and therapeutic effect of intragastric administered HA-5-HT@CeO2   nanomedicine which is constructed by using cerium dioxide nanoparticles (CeO2 NPs), serotonin (5-HT) and hyaluronic acid (HA) on ulcerative colitis (UC). Abstract : Ulcerative colitis (UC) is a chronic nonspecific inflammatory bowel disease often characterized by rapid progression and frequent comorbidities that make its treatment challenging. In colonic ulcers of UC patients, myeloperoxidase (MPO) is highly expressed, which results in an abundance of macrophages and reactive oxygen species. This study developed an active MPO-targeting hyaluronic acid/serotonin ceria nanoenzyme (HA-5-HT@CeO2 ) using the electrostatic interaction between CeO2 nanoparticles, 5-hydroxyserotonin-cerium oxide and hyaluronic acid. Based on the dual targeting effects of MPO and the macrophage CD44+ receptor in locating the inflammatory site in conjunction with the inflammatory area of the colon through electrostatic action, CeO2 nanoparticles along with multiple similar enzymes were used to eliminate O2, H2 O2 and ˙OH and other reactive oxygen species, achieving targeted repair of the intestinal epithelial barrier through the elimination of inflammatory factors. In studies involving pharmacodynamics in vitro and DSS-induced animal models of acute colitis in vivo, HA-5-HT@CeO2 has been shown to reduce inflammation further and treat ulcerative colitis compared to traditional drugs. Additionally, active targeting of MPO inflammation can lead to accurate drug delivery to the site and can minimize the side effects associated with the drug. HA-5-HT@CeO2 is a promising novel drug for the treatment of ulcerative colitis. In addition to illustrating the benefits of this novel nanodrug delivery in treating ulcerative colitis compared to traditional medications, this study provides theoretical and experimental support for its application to any targeted therapy for ulcerative colitis.